Modelling and experimenting thermal energy storage through the use of PCM in low thermal inertia office - Abreu, Duarte Drumond de (2020)
ABSTRACT: Within the scope of this thesis, thirty DuPont Energain thermal mass boards were tested inside a shipping container located in Oeiras, Portugal. These phase change material (PCM) boards have a 21.7 °C melting point and they were experimented during August (Summer) as internal mass due to a structure specifically designed for this project. Results showed that these latent heat storage systems induced an indoor peak temperatures shift of three hours and a slight indoor temperatures reduction. An EnergyPlus model was validated using measured data and several parametric studies were made using this model. In this case, it was found that the best solution for this low thermal inertia enclosure was incorporating forty eight panels with 10 mm of thickness and a melting point of 20 °C. Although these panels have a payback period of thirty two years, in the future it can fall into a more acceptable value of five years.